SPRAYING QUALITY OF CROP PROTECTION PRODUCTS USING TWO DROPLET SPECTRA IN THREE PERIODS OF THE DAY - Graziano,Carlos E. P. L. (2017)
ABSTRACT: Spraying of crop protection products can be affected by weather conditions and spray nozzles, altering deposition patterns and coverage of the target surface. The objective of this research was to analyze the quality of sprayings performed in three periods of the day (9:00 am, 2:00 pm, and 6:00 pm), using two different droplet sizes (fine and coarse) in soybeans. Coverage and deposition were evaluated in the upper, middle, and lower portion of soybean canopy. Spraying the products at 2:00 pm increased leaf coverage in the medium portion but also increased losses to the soil. Spray nozzles with fine droplet sizes provided greater coverage and deposition in the medium and upper portion of the crop for the sprayings performed in the morning. If compared to coarse droplets, fine droplets increased leaf coverage and had no interference with the losses to the soil.